The line [videorecording (Blu-Ray)] - Berger, Ethan; Wolff, Alex, 1997-; Pullman, Lewis, 1993-; Bailey, Halle, 2000-; Abrams, Austin, 1996-; Cloud, Angus, 1998-2023; Mitchell, Bo (actor); Richards, Denise, 1971-; Oteri, Cheri; McNairy, Scoot; Malkovich, John (Utopia, 2023)
"Ethan Berger's feature narrative debut is an engrossing contemplation of blind adherence to tradition through the lens of a fictional college fraternity. Tom (Alex Wolff), a passionate 'brother' of this fraternity, is charmed by the promises of high social status and alumni connections that open doors. But as a classmate outside of his social circle named Annabelle (Halle Bailey) enters his life, his devotion begins to falter. Once the scheduled hazing of new fraternity members comes to a disturbing head, Tom is faced with the decision of a lifetime."--Amazon.